Simulation of Solar-Assisted Single Stage Absorbtion Chiller as Ice Maker Based on MATLAB - Ridho Hantoro; Dwi Ganef Janesa (Institut Teknologi Sepuluh Nopember, 2015)
In this research, the system is described in the two-dimensional form to simplify the completion and modeling. There are various kinds of components, among others: evaporator, condenser, Solution Heat Exchanger (SHX), absorber, generator (including solar collector), pumps, and expansion valve.